Development of power system dynamic equivalents toolbox for digital type power system simulator - Kok, Boon Ching; Zin, Abdullah Asuhaimi Mohammad; Mustafa, Mohammad Wazir; Lo, Kwok Lun (Penerbit Universiti Sains Malaysia, 2004)
The aim of this research is to develop a power system dynamic equivalents toolbox (PSDYNET) for digital type power system simulator. In dynamics study of large power system, it is of the essence to represent the external system by means of dynamic equivalents with the intention of improve the solution speed and to reduce the problem into a solvable size.